Technical dynamic capabilities in the opinion of Polish producers from the agricultural machines sector1 - Nogalski Bogdan; Niewiadomski Przemysław; Szpitter Agnieszka (Management)
The main aim of this paper is to develop a model of key technical dynamic capabilities providing implementation flexibility of manufacturing companies of the Polish agricultural sector. Achieving the main target required to formulate sub-targets, to which the following have been included: the query of subject literature remaining in a direct relation to the topic of the research, which, in the authors’ intention, will find its expression in the developed definition of technical dynamic capabilities. At the design level, it is essential to search for the answer to the question: what technical capabilities imply dynamic flexibility of the Polish manufacturers of the agricultural machinery sector?, while, at the empirical level, to prioritize individual technical dynamic capabilities and determine what deficiencies in this area are characteristic for the studied companies.